2000
DOI: 10.1002/1096-8628(20000911)94:2<91::aid-ajmg1>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent digital fibroma, focal dermal hypoplasia, and limb malformations

Abstract: Recurrent digital fibroma of infancy generally is considered a sporadic tumor of childhood. We describe the case of a mother with recurrent digital fibroma at a young age who gave birth to a daughter with focal dermal hypoplasia, coloboma of the iris and eyelids, anal atresia, and extensive limb malformations. When the infant was 3 months old, fibromas started to appear at the fingertips. The cases of three additional patients are described, with a similar combination of multiple digital fibromas, pigmented ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…Iceland exhibits a high degree of socioeconomic heterogeneity, so the findings lend support to the theory that increases in homozygosity can enhance fertility through a variety of physiological and bio-behavioral mechanisms, provided they are relatively mild (Helgason, Pálsson, Guðb-jartsson, Kristjánsson, & Stefánsson, 2008). Consanguineous mating is known to increase the incidence of physical deformities and diseases, including childhood blindness (Baghdassarian & Tabbara, 1975), neonatal diabetes mellitus (Brickwood et al, 2003) and limb malformations (Breuning et al, 2000). A study by Jaber, Halpern, and Shohat revealed that the overall incidence of congenital malformations was 2.5 times higher amongst the offspring of consanguineous mating when compared to the offspring of non-consanguineous mating (1998).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Iceland exhibits a high degree of socioeconomic heterogeneity, so the findings lend support to the theory that increases in homozygosity can enhance fertility through a variety of physiological and bio-behavioral mechanisms, provided they are relatively mild (Helgason, Pálsson, Guðb-jartsson, Kristjánsson, & Stefánsson, 2008). Consanguineous mating is known to increase the incidence of physical deformities and diseases, including childhood blindness (Baghdassarian & Tabbara, 1975), neonatal diabetes mellitus (Brickwood et al, 2003) and limb malformations (Breuning et al, 2000). A study by Jaber, Halpern, and Shohat revealed that the overall incidence of congenital malformations was 2.5 times higher amongst the offspring of consanguineous mating when compared to the offspring of non-consanguineous mating (1998).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Fig. 7 Cryotherapy on the third toe of the right foot Table 3 Histochemical findings in fibromas associated with digitocutaneous dysplasia Inclusion bodies [11,27] Alpha-smooth actin muscular [12,27] Vimentin [6] Desmin CD10 [12] …”
Section: Discussionmentioning
confidence: 99%
“…Although the fibromas associated with DCD are known to recur after operation, they have been reported to spontaneously regress-a feature also seen in IDF. 2,4 Adult women with DCD may be left with vestigial, linear remnants of the fibromas on their fingertips. 3 Malignant transformation of fibromas does not appear to occur in either IDF or DCD.…”
Section: Discussionmentioning
confidence: 99%